INDIKASI FOTOKOAGULASI LASER PADA PASIEN RETINOPATI DIABETIK DI BALAI KESEHATAN MATA PROPINSI SULAWESI UTARA PERIODE JANUARI – DESEMBER 2012 - Tappang, Renta; Sumual, Harry; Rares, Laya (Universitas Sam Ratulangi, 2014)
Abstract: Diabetic retinopathy is one of the vascular disorders that can occur in type 1 and 2 diabetes mellitus cases after 10-15 years. Treatment of diabetic retinopathy is based on its severity; one of the treatment is laser photocoagulation.This study aimed to find out the indication of laser photocoagulation procedure among diabetic retinopathy cases at BKMM North Sulawesi Province. This was a descriptive retrospective study using the medical records of diabetic retinopathy cases who underwent laser photocoagulation. There were 35 cases as samples who underwent laser photocoagulation during January– December 2012. The results showed that most cases were proliferative diabetic retinopathy (86,6%). The most frequent age group was 41-60 years (68.6%), predominantly females (60%). Moreover, there were 80% cases who underwent one time of laser photocoagulation meanwhile the others 20% underwent more than one photocoagulation during January– December 2012. Conclusion: The most frequent indication of laser photocoagulation among diabetic retinophaty cases at BKMM North Sulawesi Province was proliferative diabetic retinopathy. Keywords: indication of laser photocoagulation, retinopathy Abstrak: Retinopati diabetik adalah suatu kelainan vaskular yang terjadi pada kasus diabetes melitus tipe 1 dan 2 setelah 10 – 15 tahun. Penatalaksanaan retinopati diabetik dibuat berdasarkan pada tingkat kelainan penyakitnya; salah satu cara ialah dengan menggunakan terapi fotokoagulasi laser. Penelitian ini bertujuan untuk mengetahui indikasi fotokoagulasi laser pada kasus retinopati diabetik di Balai Kesehatan Mata Masyarakat (BKMM) Propinsi Sulawesi Utara. Metode penelitian ini deskriptif retrospektif dengan menggunakan catatan rekam medik kasus retinopati diabetik yang telah dilakukan fotokoagulasi laser. Sampel berjumlah 35 kasus retinopati diabetik yang menjalani fotokoagulasi laser pada periode Januari – Desember 2012 dengan persentase terbanyak retinopati diabetik proliferatif (88,6%). Kelompok usia tersering 41-60 tahun (68,6%), sedangkan jenis kelamin didominasi oleh perempuan (60%). Kasus yang terbanyak (80%) ialah yang menjalani hanya satu kali fotokoagulasi laser sedangkan sisanya (20%) menjalani tindakan tersebut lebih dari satu kali. Simpulan: Pada kasus retinopati diabetik di BKMM Propinsi Sulawesi Utara indikasi tersering untuk dilakukan fotokoagulasi laser ialah retinopati diabetik proliferatif. Kata kunci: indikasi fotokoagulasi laser, retinopati